(untitled) (Baghdad Science Journal, 2010)
In this work 2-hydrazino pyrimidine (1) was prepared from 2-mercapto pyrimidine with hydrazine hydrate. Treatment of (1) with active methylene compounds gave 2-(3,5-dimethyl -1 H – Pyrazole-1-yl) pyrimidine , whereas the reaction of (1) with carboxylic anhydride namely maleic anhydride or 1,2,3,6-tetra hydro phthalic anhydride yielded 1-Pyrimidine-2-yl-1,2-dihydro pyridazine-3,6-dione (3) and 2 – Pyrimidin -2-yl -2,3,4 a ,5,8 a – hexahydro phthalazine 1,4 – dione (4) . Reaction of (1) with phenyl isothiocyanate and ethyl chloro acetate afforded 3-Phenyl-1,3-thiazolidine-2,4-dione-2( pyrimidine -2- yl hydrazone (6) Azomethine (7-10) were prepared through condensation of (1) with aromatic aldehydes or ketones, then compounds (7-9) are converted into a number of tetrazole derivatives (11-13). Treatment of (1) with acetic acid afforded the derivative (14) . The reaction of 2-mercapto pyrimidine with ethyl chloro acetate afforded (15),whereas the reaction of (15) with thiosemicarbazide and 4% sodum hydroxide leads to ring closure giving 1,2,4 triazole derivative (17). Moreover the reaction of 2-mercapto pyrimidine with chloro acetic acid gave (18) followed by refluxing (18) with o- amino aniline to give the benzimidazole derivative (19).the structure of these compounds were characterized by FR-IR, UV spectra and some of them were characterized by element analysis.